PENGARUH GOOD CORPORORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN - Eka Mustikasari; Syaefullah SE., Ak (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The study examined the effect of corporate governance on financial performance of the company. Good corporate governance was idenitifed by the number of audit commitee, the proportion of managerial ownership, the propotion of institutional ownership, the propotion of independent commissioners, board cross directorships, growth opportunity, and firm’s size. Indicators of financial performance were measured by return on equity ( ROE). The sample used 112 companies from a population of 155 companies manufacturing sector listed on the Indonesian Stock Exchange which issued GCG reports with total of observation data 224 in period 2012-2013. The sample was determined using purposive sampling The study used multiple regression analysis and processed using SPSS. The result showed that there was significant effect between audit commitees, institusional ownership, independent comissioner, and growth opportunity to financial performance. Howefer it was not found that managerial ownership, board cross directorships, and firm’s size had an influence on financial performance. Keyword : Good Corporate Governance, kinerja keuangan, return on equity (ROE)